7x-3x+2=2x+2x+8-6

Simple and best practice solution for 7x-3x+2=2x+2x+8-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x-3x+2=2x+2x+8-6 equation:


Simplifying
7x + -3x + 2 = 2x + 2x + 8 + -6

Reorder the terms:
2 + 7x + -3x = 2x + 2x + 8 + -6

Combine like terms: 7x + -3x = 4x
2 + 4x = 2x + 2x + 8 + -6

Reorder the terms:
2 + 4x = 8 + -6 + 2x + 2x

Combine like terms: 8 + -6 = 2
2 + 4x = 2 + 2x + 2x

Combine like terms: 2x + 2x = 4x
2 + 4x = 2 + 4x

Add '-2' to each side of the equation.
2 + -2 + 4x = 2 + -2 + 4x

Combine like terms: 2 + -2 = 0
0 + 4x = 2 + -2 + 4x
4x = 2 + -2 + 4x

Combine like terms: 2 + -2 = 0
4x = 0 + 4x
4x = 4x

Add '-4x' to each side of the equation.
4x + -4x = 4x + -4x

Combine like terms: 4x + -4x = 0
0 = 4x + -4x

Combine like terms: 4x + -4x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 7(3x+2)-3=2(x-2)+5 | | (3p-7)(2p+8)= | | 10x+6=-7 | | 2[3x+4]=19 | | 4n+1=36 | | 0.26x+0.07(60000-x)=11040 | | 0=5x^(2/3)-2x^(5/3) | | -2-5x+2= | | 1/2[5-x]=1/4 | | -2xy^2(3x-2y)= | | 7z-6=5 | | x^3-8x+8=0 | | 10x-5=x+8 | | 9^-5x^4/9^-3x^-1= | | 7(u-6)=-7 | | 5x-3x-24=8x-2x+24 | | 43/29=24/x | | =32-[9-3(4-10)]+(2-5)3 | | 12+6x=8-4x | | 8[x+6]-3x=18 | | 18(v+1)-2v=4(4v+4)-21 | | 6(7x-8)=246 | | (-4x^2y)(3x^4)(-2xy^5)= | | 3+8z-12=2z-9+z | | 8(5x-11)=112 | | 5x^2+9x-165=0 | | 10(7x+14)=490 | | 6(7x+6)=246 | | -9(v+3)+2v+7=5v+11 | | Sin^2(x)+9sin(x)+8=0 | | (2x+3)(3x^2-2x+1)= | | 6n=0.84 |

Equations solver categories